ANALISIS PARAMETER KEGEMPAAN a-VALUE DAN b-VALUE DI PROVINSI SULAWESI UTARA PERIODE 2019-2023 - Sangi, Monika Siska; Palilingan, Rolles N; Sompotan, Armstrong F.; Manado, Stasiun Geofisika (LPPM Politeknik Saint Paul Sorong, 2024)
Indonesia is an area that is prone to natural disasters, one of which is earthquakes. Several strong earthquakes have occurred in North Sulawesi, causing extensive structural damage. This study aims to determine the seismicity parameter values a-value and b-value or to determine the level of fragility and seismicity in North Sulawesi. The earthquake data used is secondary data for the period 2019-2023 obtained from the Manado Geophysical Station, BMKG, North Sulawesi. The data obtained includes the date, time of occurrence, latitude, longitude, magnitude and depth of the earthquake. This study uses the Guttenberg-Richter method which is processed using Zmap software. From the distribution of earthquake data, it is known that a major earthquake occurred in 2019 with a magnitude of 7.1. The results of this study show that in 2019 it had a high a-value, namely 8.13. This shows that in 2019 in the North Sulawesi area there were relatively more earthquakes. The b-value results in this study show that in 2022 it has a high b-value, which is 1.32. This is influenced by elastic rocks that experience stress so that there is a change in shape or deformation called rock fragility. Seismicity vulnerability in the North Sulawesi region for the period 2019-2023 ranges from 6.16 to 8.13 with a rock fragility level range from 0.91 to 1.32